Epidural analgesia does not impact recurrence or mortality in patients after rectal cancer resection - Hsiang-Ling Wu; Ying-Hsuan Tai; Shih-Pin Lin; Shung-Haur Yang; Mei-Yung Tsou; Kuang-Yi Chang (Scientific Reports, 2021)
Abstract The relationship between epidural analgesia and rectal cancer outcome is not fully clarified. We aimed to investigate the putative effect of epidural analgesia on the risks of recurrence and mortality after rectal tumour resection. In this monocentric cohort study, we consecutively enrolled patients with stage I–III rectal cancer who underwent tumour resection from 2005 to 2014. Patients received epidural analgesia or intravenous opioid-based analgesia for postoperative pain control. Primary endpoint was first cancer recurrence. Secondary endpoints were all-cause mortality and cancer-specific mortality. We collected 1282 patients in the inverse probability of treatment weighting analyses, and 237 (18.5%) used epidurals. Follow-up interval was median 46.1 months. Weighted Cox regression analysis showed the association between epidural analgesia and recurrence-free survival was non-significant (adjusted hazard ratio [HR] 0.941, 95% CI 0.791–1.119, p = 0.491). Similarly, the association between epidural analgesia and overall survival (HR 0.997, 95% CI 0.775–1.283, p = 0.984) or cancer-specific survival (HR 1.113, 95% CI 0.826–1.501, p = 0.482) was non-significant either. For sensitivity tests, quintile stratification and stepwise forward model selection analyses showed similar results. We did not find a significant association between epidural analgesia and risk of recurrence, all-cause mortality, or cancer-specific mortality in patients with rectal cancer undergoing tumour resection.